PELAKSANAAN DIALOG KESEHARIAN UNTUK MENEMUKAN MATERI PEMBELAJARAN YANG RELEVAN DAN BERMAKNA DENGAN BANTUAN AI STUDI KASUS PADA FASE C, SD KANISIUS KENALAN, BOROBUDUR, MAGELANG, JAWA TENGAH - Bramasti, Danang (Spiritualitas Ignasian: Jurnal Kerohanian dalam Dunia Pendidikan, 2025)
The purpose of this paper is to describe the application of dialogic learning as a method for discovering learning materials based on students’ lived experiences. Through dialogue, students are positioned as the subjects of learning, while teachers act as dialogue partners, facilitators, and designers of the learning process. The results of these dialogues are used by teachers to design learning based on the Reflective Pedagogy Paradigm (PPR), with the assistance of artificial intelligence (AI). This research method uses a descriptive qualitative approach, with two teachers and seventeen Phase C students at Kanisius Kenalan Elementary School, Borobudur, Magelang as the primary participants. Data collection was conducted through observation, interviews, and photo and video documentation. Data analysis focused on the stages of dialogue, the pedagogical shift by placing students at the center of learning, and the relevance of the resulting learning materials. The results demonstrate that dialogue plays a crucial role in discovering meaningful, contextual, and reflective learning.